Essential and toxic elements analysis of wild boar tissues from north-eastern Romania and health risk implications - Boișteanu, Paul-Corneliu; Flocea, Elena-Iuliana; Anchidin, Bianca-Georgiana; Mădescu, Bianca-Maria; Matei, Mădălina; Murariu, Otilia Cristina; Frunză, Gabriela; Postolache, Alina Narcisa; Ciobanu, Marius-Mihai (Frontiers in Sustainable Food Systems, 2024)
The level of essential minerals in meat is an important factor in human nutrition and health. Meat from responsibly managed wildlife is an alternative raw material with considerable nutritional benefits. Meat from hunted animals has essential and non-essential elements for the human body. It is important to carefully monitor the levels of heavy metals accumulated in the tissues of hunted animals in polluted areas to ensure food safety and environmental contamination. High levels of heavy metals in food and the environment can pose a danger to human health.